Safety and efficacy of a combined paste formulation of a botanical extract of the latex of Croton lechleri (SB-300, Neonorm foal™) with probiotics for the treatment of watery diarrhea in nursing foals - McAuliffe, Siobhan (2017)
Diarrhea is a common disorder in preweaned foals, and there are no antisecretory antidiarrheals currently available. The objective of this study was to evaluate the safety and efficacy of an enteric-coated paste formulation of a standardized botanical extract of the latex of Croton lechleri (SB-300) for the treatment of watery diarrhea in foals. This was a randomized blinded multisite, safety and efficacy pilot study of the formulation in client-owned foals with watery diarrhea. Sixty-one foals under 16 weeks of age with watery diarrhea were randomly divided into two treatment groups and one placebo group, approximately 20 foals each. Each foal received either placebo or investigational product/probiotic combination, four times daily. No significant safety issues were noted but the transient production of hard feces that was noticed in foals that continued therapy beyond clinical improvement. A treatment responder was any foal who developed formed stool (fecal score <3), and maintained formed stool for a minimum of 16 consecutive hours within a 24 h period. Statistically significant differences in treatment response were demonstrated at a number of time points between the investigational product treatment and placebo groups. We conclude that a paste formulation of SB-300, a standarized botanical extract of the latex of Croton lechleri, when combined with probiotics, is effective in the treatment of watery diarrhea in foals less than 16 weeks of age and warrants further investigation without the addition of probiotics.